(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper examines the need and significance of green marketing . This paper attempts to capture some of these initiatives in India, which may provide ideas for other companies in both developing and developed markets and evaluates the challenges and strategies faced by the Indian companies and their concern for green marketing to tackle social and environmental problem using innovative solutions. Green marketing is a vital constituent of the holistic marketing concept today. It is particularly applicable to those businesses that are directly dependent on the physical environment. Changes in the physical environment may pose a threat to fishing, processed foods tourism and adventure sports industries. Consequently new types of products were created, called green products, which would cause less damage to the environment. Thus green marketing plays an important role to promote and reinforce the idea of environmental protection and sustainable development both in the minds of the customer and the firms.Many global players in diverse businesses are now successfully implementing green marketing practices .Various studies by environmentalists indicate that people are concerned about the environment and are changing their behavioral pattern. The most of the consumers, both individual and industrial, are becoming more concerned about environment-friendly products. Majority of them feel that environment-friendly products are safe to use. As a result, green marketing has emerged, which aims at marketing sustainable and socially-responsible products and services. Now is the era of recyclable, non-toxic and environment-friendly goods. This has become the new mantra for marketers to satisfy the needs of consumers and earn better profits.Green marketing is the process of developing products and services and promoting them to satisfy the customers who prefer products of good quality, performance and convenience at affordable cost, which at the sometime do not have a detrimental impact on the environment. It includes a broad range of activities like product modification, changing the production process, modified advertising, change in packaging etc., aimed at reducing the detrimental impact of products and their consumption and disposal on the environment. Companies all over the world are striving to reduce the impact of products and services on the climate and other environmental parameters. Marketers are taking the cue and are going green. Thus there is growing interest among the consumers all over the world regarding protection of environment in which they live People do want to bequeath a clean earth to their offspring. Worldwide evidence indicates people are concerned about the environment and are changing their behavior. As a result of this, green marketing as emerged which speaks for growing market for sustainable and socially responsible products and services.